Mental health need and psychiatric service utilization patterns of refugee children in Turkey: A comparative study - BEŞER, CAN; FADILOĞLU, ERAY; PERDAHLI FİŞ, NEŞE (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Objective: Turkey is hosting three and a half million of refugee people from Syria and it is the leading refugee hosting country. Despite previous study findings indicating high rates of psychiatric morbidity among refugee children, little is known about the mental health service utilization patterns of refugee children in Turkey. We aimed to investigate psychiatric service utilization pattern and clinical profiles of refugee children and compare the findings with non-refugee children who applied to the same child psychiatry service in Istanbul. Method: We determined sociodemographic characteristics, psychiatric diagnoses, and the number of visits among refugee children in comparison to non-refugees. Predictors of early dropout in refugees were analysed using logistic regression. Results: Our sample comprised 91 refugee children (31.9% female, mean age = 9.02 years) and 82 non-refugees (34.1% female, mean age = 9.32 years). A broad range of war-related traumatic events was reported by the refugee children. The most prevalent traumatic events were hearing shootings or blasts (87.3%), witnessing clashes or bombardment (68.8%), and exposing to corpses or mutilated bodies (33.3%). Even though depression (28.6%) and posttraumatic stress disorder (PTSD) (22%) were more common among refugee children, ADHD (36.3% in refugee vs. 47.6% in non-refugee) was the most common disorder in both groups. Refugee children were attended fewer appointments for mental healthcare than non-refugee children (p < 0.05). Logistic regression analysis revealed that the lower likelihood of early dropout from mental healthcare service were associated with having ADHD (OR 0.229, 95%C.I: 0.066?0.798) and PTSD (OR 0.125, 95%C.I:0.030?0.520) diagnoses in refugee group. Conclusions: Our findings highlighted that clinicians and service providers should be aware of refugees? complex mental health needs and social difficulties. To provide effective mental health services for refugee children, it is crucial to develop policies facilitating the access to the services and increasing the treatment adherence.
Keywords: Refugee children; Mental health; Psychiatric disorders; Service utilization; Posttraumatic stress disorder; POSTTRAUMATIC-STRESS-DISORDER; UNITED-STATES; TRAUMA; RISK; CARE